2021
DOI: 10.1038/s41385-021-00412-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and function of the epithelial cell-specific ER stress sensor IRE1β

Abstract: Barrier epithelial cells lining the mucosal surfaces of the gastrointestinal and respiratory tracts interface directly with the environment. As such, these tissues are continuously challenged to maintain a healthy equilibrium between immunity and tolerance against environmental toxins, food components, and microbes. An extracellular mucus barrier, produced and secreted by the underlying epithelium plays a central role in this host defense response. Several dedicated molecules with a unique tissue-specific expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 112 publications
0
23
0
1
Order By: Relevance
“…2 In line with its tissue-specific expression, IRE1β has been implicated in mucin production in both lung and gut epithelia. 2 As mucus overproduction is an important clinical feature in many asthma patients, 3 IRE1β may pose an attractive pharmacological treatment option. In ovalbumin (OVA)induced experimental asthma, IRE1β regulates mucin production through splicing of XBP1 4 ; however, its role in the more physiologically relevant house dust mite (HDM) model remains as yet unexplored.…”
Section: R E Fe R E N C E Smentioning
confidence: 99%
See 2 more Smart Citations
“…2 In line with its tissue-specific expression, IRE1β has been implicated in mucin production in both lung and gut epithelia. 2 As mucus overproduction is an important clinical feature in many asthma patients, 3 IRE1β may pose an attractive pharmacological treatment option. In ovalbumin (OVA)induced experimental asthma, IRE1β regulates mucin production through splicing of XBP1 4 ; however, its role in the more physiologically relevant house dust mite (HDM) model remains as yet unexplored.…”
Section: R E Fe R E N C E Smentioning
confidence: 99%
“…based endonucleases that generate the transcription factor X-box binding protein 1 (XBP1)s through splicing of Xbp1 mRNA. 2 In line with its tissue-specific expression, IRE1β has been implicated in mucin production in both lung and gut epithelia. 2 As mucus overproduction is an important clinical feature in many asthma patients, 3 IRE1β may pose an attractive pharmacological treatment option.…”
Section: R E Fe R E N C E Smentioning
confidence: 99%
See 1 more Smart Citation
“…COPD patients have more mucus cells in their respiratory tract, often secreting a lot of mucus. IRE1 β (inositol-requiring enzyme 1beta) of airway goblet cells plays an important role in mucin cell phenotype and secretion of mucin5AC and mucin5B ( Cloots et al, 2021 ). Michael found that in HEK293 cells models with purified protein, IRE1 α is closely related with IRE1 β diminishing expression and inhibiting signaling.…”
Section: Endoplasmic Reticulum Stress In Pulmonary Diseasementioning
confidence: 99%
“…Metazoans have two IRE1 paralogues, IRE1α (referred to as IRE1 in this paper) and IRE1β. While IRE1α is ubiquitously expressed, IRE1β expression is restricted to gastrointestinal epithelium (Cloots et al , 2021 ). To date, IRE1 has been described to trans‐ autophosphorylate as a first step in the activation of its RNase modality, which initiates a nonconventional RNA‐splicing reaction and the production of the transcription factor known as spliced X box protein‐1 (XBP1s), which is one of the key drivers of the unfolded protein response (UPR) (Walter & Ron, 2011 ; Çimen et al , 2016a ; Robblee et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%